2017
DOI: 10.1039/c6ra24947g
|View full text |Cite
|
Sign up to set email alerts
|

The positive role of (NH4)3AlF6 coating on Li[Li0.2Ni0.2Mn0.6]O2 oxide as the cathode material for lithium-ion batteries

Abstract: A Li-rich cathode material Li1.2Ni0.2Mn0.6O2 coated with (NH4)3AlF6 and its enhanced electrochemical cycling performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Similar strategies have been applied to suppress the harmful interaction between electrode materials and electrolytes for lithium ion batteries. [11][12][13] The alumina coating for lithium cobalt uorophosphate was reported to prevent metal ion dissolution and improve the cycle performance. 14 A widely recognized interpret is that the alumina coating can protect cathode materials from hazardous reaction products such as HF obtained during the charge-discharge process.…”
Section: Introductionmentioning
confidence: 99%
“…Similar strategies have been applied to suppress the harmful interaction between electrode materials and electrolytes for lithium ion batteries. [11][12][13] The alumina coating for lithium cobalt uorophosphate was reported to prevent metal ion dissolution and improve the cycle performance. 14 A widely recognized interpret is that the alumina coating can protect cathode materials from hazardous reaction products such as HF obtained during the charge-discharge process.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that NH 4 + existed in the reaction process from the beginning to the end . It has been reported that (NH 4 ) 3 AlF 6 could enhance the reversible capacity and cycling performance of SCs when it is coated on cathode material …”
Section: Resultsmentioning
confidence: 88%
“…Composition [29][30][31][32][33][34][35][36] Compared to LLO (4.79114 Å), a considerable d-spacing shift in the c-axis direction can be detected in the LLO-500 sample (4.78117 Å), which can be ascribed to the pre-introduced oxygen vacancies and shrinkage of the layer structure in LLO-500 (Supporting Information, Figure S1a ). Comparison of the d-spacing changes of the various post-annealed samples, including LLO, LLO-200, LLO-300, LLO-400, LLO-500, LLO-600, shows that the LLO-500 sample displays the largest d-spacing change due to OVs formation (see Supporting Information, Figure S1b).…”
Section: Resultsmentioning
confidence: 99%